State Regulation of Trade Disputes in Essential Services in Nigeria - Fashoyin, Tayo (Relations industrielles / Industrial Relations, 1981)
This paper examines the management of trade disputes in essential services in Nigeria and identifies two settlement approaches which are seen to have the opposite effects to those in-tended.